2017
DOI: 10.1186/s12985-017-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of siRNAs derived from Southern rice black-streaked dwarf virus in infected rice and their potential role in host gene regulation

Abstract: BackgroundVirus-derived siRNAs (vsiRNAs)-mediated RNA silencing plays important roles in interaction between plant viruses and their hosts. Southern rice black-streaked dwarf virus (SRBSDV) is a newly emerged devastating rice reovirus with ten dsRNA genomic segments. The characteristics of SRBSDV-derived siRNAs and their biological implications in SRBSDV-rice interaction remain unexplored.MethodsVsiRNAs profiling from SRBSDV-infected rice samples was done via small RNA deep sequencing. The putative rice target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 80 publications
(117 reference statements)
7
27
0
Order By: Relevance
“…Consistent with previous report for diverse plant-virus-specific sRNAs (Donaire et al, 2008; Lan et al, 2018b; Xu and Zhou, 2017), CymMV and ORSV siRNAs also demonstrated a clear tendency to begin with uracil (U), adenine (A), as compared with cytosine (C) and guanidine (G) (Fig. 2E and F).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous report for diverse plant-virus-specific sRNAs (Donaire et al, 2008; Lan et al, 2018b; Xu and Zhou, 2017), CymMV and ORSV siRNAs also demonstrated a clear tendency to begin with uracil (U), adenine (A), as compared with cytosine (C) and guanidine (G) (Fig. 2E and F).…”
Section: Resultssupporting
confidence: 92%
“…USPs can increase adversity tolerance of plants (Sinha et al, 2016). Besides, our results revealed that 4 target genes (DCL1, argonaute16, RdRP-SHL2, and piRNA biogenesis protein EXD1) were annotated as core components of RNAi response (Table 2), suggesting RNAi response may be targeted and its expression levels be further suppressed by vsiRNAs generated in P. equestris infected with CymMV and ORSV, which is similar to other host-pathogen systems (Xu and Zhou, 2017). Many intracellular pathogens, including viruses, parasites, and bacteria, invade, replicate, spread within and exit their host cells in a cytoskeleton-dependent manner (Gouin et al, 2005; Greber and Way, 2006; Gruenheid and Finlay, 2003).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Among which, DCL4-dependent 21-nt vsiRNAs play a dominant role in positive-sense RNA virus-infected plants, whereas DCL2-dependent 22-nt vsiRNAs, can substitute for DCL4 when the expression of DCL4 is inhibited [53,56]. VsiRNAs pro ling of Southern rice black-streaked dwarf virus (SRBSDV)-infected rice plants showed that 21-and 22-nt were the most abundant vsiRNAs, supposed that DCL4 and DCL2 are the primary RNA silencing component for generating vsiRNAs [57]. The vsiRNAs obtained from Rice black-streaked dwarf virus (RBSDV) infected maize and rice plants accumulated preferentially as 21-and 22-nt [58,59].…”
Section: Discussionmentioning
confidence: 99%